Assessment of Human-originated Medroxyprogesterone Acetate (MPA) as Effective Contraceptive in Domesticated Queens (Felis catus) in Iraq - A Alabodi, Mushtaq; M Almeeni, Imad (The Iraqi Journal of Veterinary Medicine, 2024)
Domestic cats (Felis catus) pose a significant challenge for pet owners during the mating season, necessitating effective contraceptive strategies to manage feline populations. This study investigated the use of medroxyprogesterone acetate (MPA), precisely the human formulation Depo-Provera®, as a potential solution for feline contraception. Ten adult female cats were included in a randomized controlled trial, with the treatment group receiving a single intramuscular injection of 25 mg/cat MPA. Clinical observations, vaginal cytology, and hormonal analysis were conducted to assess treatment efficacy. Results demonstrated that MPA treatment effectively suppresses estrus behaviours, prolongs interestrus duration, and modulates hormonal profiles (estrogen, progesterone, and prolactin). This indicates its promise as a safe and practical contraceptive option for managing feline populations. This study provided a viable, non-invasive alternative for feline population control. Further research is recommended to optimize dosing regimens and evaluate long-term effects on reproductive health‎‎‎.